Photoperiodism the biological calendar - Nelson, Randy Joe.; Denlinger, David L.; Somers, David E., 1954- (New York ; Oxford : Oxford University Press, 2010)
This book examines the role of photoperiod (day length) in timing seasonal adaptations in plants, invertebrates, and vertebrates. Current literature is distinctly separated among researchers working with these different taxa, resulting in inefficiency and redundancies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Photoperiodism